The Influence of Marketing Mix on Buying Decisions at Dunia Dolls Stores Medan - Dedy Lazuardi; Ihdina Gustina (Outline Publisher, 2023)
This study aims to determine the effect of products on purchasing decisions in the world of dolls, determine the effect of prices on purchasing decisions in the world of dolls, and determine the effect of products and prices on purchasing decisions in dolls world The research population that will be used in the study are all consumers who made purchases at the company during the 2020 period as many as 716 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 88 respondents. The results showed that the product and price partially had a positive and significant effect on the consumer purchasing decisions of the Doll World. The results showed that the product and price simultaneously had a positive and significant effect on the consumer purchasing decisions of the Doll World. The results of this study are supported by the value of R square (R2), which means that product and price have an influence on purchasing decisions. While the rest is influenced by other factors that come from outside this research model such as location, product design, price discount, service, loyalty, satisfaction, service and other variables.